Association of Maternal Gestational Weight Gain With Left Ventricle Geometry and Function in Offspring at 4 Years of Age: A Prospective Birth Cohort Study - Wang, Jian; Du, Bowen; Wu, Yujian; Li, Zhuoyan; Chen, Qian; Zhang, Xi; Zhang, Lin; Ye, Yujiao; Wu, Yurong; Chen, Sun; Sun, Kun (Frontiers in Pediatrics, 2021)
Background: Maternal gestational weight gain (GWG) may be associated with cardiovascular diseases in the offspring from childhood to adulthood. We aimed to investigate the association between maternal GWG and the left ventricle (LV) geometry and function in the offspring, and explore the influence of the intrauterine environment on early childhood cardiac change. Methods: Data of 981 mother-offspring pairs from the Shanghai Birth Cohort was used. Maternal pre-pregnancy weight and height, weight in the first trimester (≤12 weeks), and before delivery were measured. The echocardiography, blood pressure, and anthropometry assessment were evaluated in the offspring at 4 years of age. Results: Interventricular septal thickness during diastole had a significantly positive correlation with total GWG [β=0.009, (0.001, 0.017)]. In the second and third trimester, LV mass index [β=0.149, (0.015,0.282)], interventricular septal thickness in systole [β=0.027, (0.011,0.043)], and in diastole [β=0.014, (0.005,0.023)] were positively associated with GWG. The risks of eccentric [OR=1.115, (1.232,1.010)] and concentric hypertrophy [OR=1.133, (1.259,1.018)] increased with the elevation of maternal GWG. Conclusions: This study suggested that the excessive maternal GWG was associated with the thickening of the interventricular septum in the offspring, especially during the second and third trimesters. Excessive GWG in the second and third trimesters was a risk factor for LV eccentric and concentric hypertrophy in the offspring.